PEMBERDAYAAN USAHA HASIL PERKEBUNAN KELOMPOK WANITA TANI (KWT) SEKAR JEPUN DI DESA KUBU, KABUPATEN BANGLI - Ida Ayu Dinda Priyanka (LPPM Institut Desain dan Bisnis Bali, 2023)
Kubu Village, Bangli District, Bangli Regency, which is famous for its diversity of tourism potential, including natural tourism potential and tourism village potential which is used as an attraction for tourists to visit. Not only is it famous for its tourism village potential, Kubu Village has considerable potential for its plantation products. The Farmer Women's Group (KWT) Sekar Japan is a group of mothers who work as housewives and farmers every day. The empowerment of the women farmer group is to process the plantation products they own. The processed plantation products are into food products such as moringa leaf tea, coffee powder and trijata flower jam. The plantation product processing business engaged in by the women farmer group in Kubu Village often experiences ups and downs in its journey. The problems faced by the Sekar Jepun Women Farmers Group are 1) partners do not understand online marketing using websites, 2) partners do not have proper financial records. 3) Limited capital so that partners often experience difficulties in meeting the needs of bamboo raw materials and supporting materials. The solutions provided to help partner problems are 1) creating and assisting in making websites 2) socializing digitalized financial records and 3) Provision of Production Supporting Facilities and Infrastructure.